The hybrid car with waste gas recovery - Mohiuddin, A. K. M. (s.n, 2012)
This report provides the detailed information involved in the design and fabrication of the Second generation IIUM buggy car. Included are all details regarding the method of design, design’s philosophy, concept and model construction, result evaluation, and fabrication process. Background research and literature review have been done in order to provide a basic reference for this buggy car design. Correct material selections and its dimensions can reduce the overall weight of the car while accurate design collaboration within the suspension system can ensure a better maneuver characteristic. A number of design options have been generated. The best choice was based on a lightweight buggy car with high strength performance, good handling characteristic, and also considering excellent driver’s ergonomic aspect.